An extension of the Benefit Risk Assessment of VaccinEs toolkit to evaluate Comirnaty and Spikevax vaccination in the European Union. - Loedy, Neilshan; Dorta, Hector G; Abrams, Steven; Crèvecoeur, Jonas; Morales, Daniel R; Cohet, Catherine; Willem, Lander; Molenberghs, Geert; Hens, Niel; Kurz, Xavier; Quinten, Chantal; Verbeeck, Johan (European Journal of Public Health, 2025)
Amid the global COVID-19 pandemic, vaccines were conditionally authorized for human use to protect against severe infection. The Benefit Risk Assessment of VaccinEs (BRAVE) toolkit, a user-friendly R Shiny application, was developed retrospectively together with the European Medicine Agency (EMA) with the aim of fulfilling the need for flexible tools to assess vaccine benefits and risks during and outside a pandemic situation. This study employed BRAVE to evaluate the impact of COVID-19 mRNA vaccines across 30 European Union (EU)/EEA countries by quantifying the number of prevented clinical events [i.e. confirmed infections, hospitalizations, intensive care unit (ICU) admissions, and deaths], using a probabilistic model informed by real-time incidence data and vaccine effectiveness estimates. The analysis assumes fixed population dynamics and behaviour. Additionally, BRAVE assesses risks associated with mRNA-based vaccines (myocarditis or pericarditis) by comparing observed incidence rates in vaccinated individuals with background incidence rates. mRNA vaccines were estimated to directly prevent 11.150 million [95% confidence interval (CI): 10.876–11.345] confirmed COVID-19 infections, 0.739 million (95% CI: 0.727–0.744) COVID-19 hospitalizations, 0.107 million (95% CI: 0.104–0.109) ICU admissions, and 0.187 million (95% CI: 0.182–0.189) COVID-19-related deaths in the EU/EEA between 13 December 2020 and 31 December 2021. Despite increased vaccination-associated myocarditis or pericarditis observed in younger men, the benefits of vaccination still outweigh these risks. Our study supports the benefit/risk profile of COVID-19 vaccines and emphasizes the utility of employing a flexible toolkit to assess risks and benefits of vaccination. This user-friendly and adaptable toolkit can serve as a blueprint for similar tools, enhancing preparedness for future public health crises.